Peran Industri Pariwisata dan Ekonomi Kreatif di Pulau Sumatera Pasca Pandemi Covid-19 - Faradis, Royhan; Suwandana, Endan (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2023)
One of the economic recovery strategies after Covid-19 pandemi in Indonesia, especially Sumatra, is to focus on the development of the real sector. Tourism and creative economy (parekraf) industry is a form of transformation of the real sector with good prospects. The question of this research is whether the parekraf industry plays a role in the economic recovery of the real sector in Sumatra Island. The methods used to answer the above questions are multiple linear regression and descriptive statistics. In addition, the cluster analysis method is also used in this study to answer which provinces need priority development of the parekraf industry. An interesting finding from this study is that the parekraf industry has played a role in restoring Sumatra's economy after Covid-19, which is proved by the significance level of 0.025. Another interesting finding is that that provinces with archipelago topography, i.e. Riau Islands and Bangka Belitung Islands, give higher economic contribution to GDRP than non-archipelago provinces in Sumatra Island.